THE EFFECT OF GIVING BANANA WASTE POC ON THE PRODUCTION OF SEVERAL VARIETIES OF SHALLOTS - Luta, Devi Andriani; Br. Sitepu, Sri Mahareni; Mutia ZNA, Hanifah (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
In increasing the growth and production of shallots, proper cultivation techniques are needed, one of which is the use of several varieties of shallots and the application of banana waste POC. This study aims to determine the growth rate and production of several varieties of shallot plants due to the administration of banana waste POC. This research was conducted in Sunggal North Sumatra from February to April 2022. This study used a factorial randomized block design (RAK) with 2 factors. The first factor is the Variety test (V) which consists of V1 = Super Philips V2 = Bauji, V3 = Bima Brebes and V4 = Maja Cipanas. The second factor is the application of POC banana weeds (B) which consists of B0 = 0 ml/L water/plot, B1 = 150 ml/L water/plot, B2 = 300 ml/L water/plot and B3 = 450 ml/L water /plots. Keywords: Shallots, Banana Waste POC, Production and varieties